O aluno na sociedade do cansaço: uma proposta pedagógico-didática para os alunos do ensino médio - Guimarães, Victor Anequim (2025)
This research investigates the repercussions of the "Society of Fatigue," as conceptualized by Byung-Chul Han, on Brazilian high school students immersed in a digital and neoliberal context. It argues that the transition from a disciplinary society, focused on negativity and external coercion, to a performance society, marked by an excess of positivity, the performance imperative ("Yes, we can"), and psychopolitics, induces individuals into self-exploitation. The contemporary student, pressured by results, competition, and the constant optimization of the self as an "entrepreneur of the self," becomes vulnerable to neuronal illnesses such as burnout, depression, and anxiety. The work analyzes how this scenario, intensified by digital technologies that promote hyperconnectivity and superficiality, configures a paradox of freedom, where apparent autonomy masks new forms of subjection. The central objective is to critically analyze this reality and propose Philosophy teaching as a space for resistance. It is proposed that, through a pedagogical approach that values contemplation, pause, and critical thinking, Philosophy can equip students to understand and question the mechanisms of the performance society. The study links this proposal with specific skills from the Humanities and Applied Social Sciences area of the National Common Curricular Base (BNCC), such as EM13CHS101 (source analysis), EM13CHS103 (argument elaboration), EM13CHS202 (technology impacts), EM13CHS401 (social relations and technology), EM13CHS404 (work transformations), EM13CHS503 (identification of violence), and EM13CHS504 (ethical-political impasses of technology). The methodology involves the analysis of Han's concepts and their application to the Brazilian educational context, using the BNCC as a reference for an engaged philosophical practice. It concludes on the urgency of rethinking educational models, countering incessant acceleration and productivity with the valorization of negativity (pause, reflection), alterity, and critical autonomy, forming subjects capable of building a more humane and less exhausting future. As a product of this research, a pedagogical e-book entitled "The Student in the Society of Fatigue: A Pedagogical-Didactic Proposal for High School" was developed, which materializes the theoretical reflections into practical proposals for pedagogical intervention. The e-book presents four structured 60-minute classes, articulating Han's concepts with specific BNCC skills, offering educators concrete tools to implement a pedagogy of negativity that values contemplation, critical reflection, and resistance to the imperatives of the performance society.